Study on the development of mobility to gymnast 10-12 years - Butu, I. M.; Teodorescu, S. A.; Catuna, C.; Alupoaie, M. (Science, Movement & Health, 2015)
Aim. We are researching disposition and qualities conducive to high performance sport, especially mobility elements necessary to achieve high amplitude of rhythmic gymnastics. Methods: Testing of specific motor skills rhythmic gymnastics (scapular-humeral joint mobility, mobility in the hip joint, spinal mobility) on a group of 11 sports (experimental group) practicing rhythmic gymnastics and another group of 29 students (control group) who do not practice sports. Results: The tests performed in the two groups is observed that athletes have achieved superior results compared to female students in the control group. Conclusions: It is found that the mobility in joints is better to athletes tested in the experimental group compared to female students who do not practice this sport, that due to the large number of hours allocated for the development of this specific motor skills.